2022
DOI: 10.1096/fasebj.2022.36.s1.r5646
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PECAM‐1 Significantly Delays Leukocyte Extravasation into the Subcortex Post‐Stroke

Abstract: Background and PurposeCurrent therapies for ischemic stroke focus on reperfusion but do not address the acute inflammatory response that results in significant reperfusion injury. To advance future therapies, a thorough understanding of the precise spatiotemporal underpinnings of leukocyte extravasation and infiltration is necessary. We describe the evolution of the inflammatory response in a mouse transient middle cerebral artery occlusion (tMCAO) stroke model at several time points after reperfusion and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Multiple approaches have been used to try and reduce such extravasation. Recently, Arias et al [ 152 ] found that a PECAM-1 neutralizing antibody reduces leukocyte influx and affects their spatial distribution within brain. BBB disruption occurs after stroke and it contributes to neuroinflammation and edema formation.…”
Section: Neurological Disordersmentioning
confidence: 99%
“…Multiple approaches have been used to try and reduce such extravasation. Recently, Arias et al [ 152 ] found that a PECAM-1 neutralizing antibody reduces leukocyte influx and affects their spatial distribution within brain. BBB disruption occurs after stroke and it contributes to neuroinflammation and edema formation.…”
Section: Neurological Disordersmentioning
confidence: 99%
“…It facilitates the final steps of leukocyte migration through the 10.3389/fnmol. 2023.1286351 endothelial cell junctions post-stroke (Arias et al, 2022). PECAM-1 plays a role in transmitting survival signals in endothelial cells, preventing apoptosis (Gao et al, 2003).…”
Section: Adhesion Moleculesmentioning
confidence: 99%
“…Platelet-Endothelial Cell Adhesion Molecule-1 (PECAM-1/CD31) is an immunoglobulin-like cell adhesion molecule expressed on the surface of endothelial cells, platelets, neutrophils, and some subsets of lymphocytes ( Arias et al, 2022 ; Fu et al, 2023 ). It facilitates the final steps of leukocyte migration through the endothelial cell junctions post-stroke ( Arias et al, 2022 ).…”
Section: Inflammatory Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Blocking PECAM after the onset of a stroke has been shown in various studies to reduce severity in murine models, pointing to PECAM's potential as a therapeutic target to mitigate neuroin ammation and aid in cerebral recovery post-IS. 8,9 While elevated levels of EpCAM and PECAM post-IS are documented, the direct causal relationship between these increased serum levels and the stroke event remains to be fully unraveled. Mendelian randomization (MR), employing genetic variations as instrumental variables, is a robust approach for ascertaining the causative impact of risk factors on disease.…”
Section: Introductionmentioning
confidence: 99%